The Longitudinal Association of Late-Life Visual and Hearing Difficulty and Cognitive Function: The Role of Social Isolation. (October 2022) - Yorgason, Jeremy B.; Tanner, Corinna Trujillo; Richardson, Stephanie; Hill, Melanie M.Y. Serrao; Stagg, Brian; Wettstein, Markus; Ehrlich, Joshua R.
Objectives: Sensory impairments are prevalent among older adults and have been associated with cognitive challenges in later life, yet mechanisms are less well understood. We examined the mediating role of social isolation in the longitudinal relationship between self-reported sensory difficulty and impaired cognitive functioning among older adults. Methods: Data were taken from the NHATS Study, an annual survey of Medicare beneficiaries' age ≥ 65. Participants ( N = 6, 338) provided data at Rounds 5, 6, and 7 (2015, 2016, 2017). Structural equation models were estimated to test longitudinal direct and indirect associations. Results: All sensory difficulties were negatively associated with all cognitive functioning measures cross-sectionally through social isolation. Longitudinally, vision difficulty and dual sensory difficulty were indirectly associated with cognitive functioning across time. Hearing difficulty had no longitudinal indirect associations with cognitive functioning through social isolation. Discussion: Social isolation is an important pathway through which late-life vision difficulty is associated with decreased cognitive function.